The Effect of Visualization of Tiktok Content Videos and OOTD Style Content on Interest in Buying Fashion for Adolescent Village Karya Makmur - Oktaviani, Dina; Susilo, Agus (Proceedings International Conference on Education Innovation and Social Science, 2022)
This study was conducted with the aim of finding out 1) whether there is an effect of visualizing TikTok content videos on the interest in buying fashion for village youth by Makmur, 2) whether there is an effect of OOTD Style creator content on buying interest in fashion for village youths by Makmur, 3) whether there is an effect of video visualization of TikTok content and OOTD Style of creator content on interest in buying fashion for village youth by Makmur. The sample in this study amounted to 171 respondents. This study uses a quantitative method with a comparative causal survey approach. Sampling technique used non-probability sampling with Quota sampling where the researcher took samples from the population that met the requirements. The data collection tool used in this research is the Likert scale in the form of a questionnaire. The data analysis technique used is multiple linear regression analysis. The results showed that 1) there was a positive and significant effect of visualizing TikTok video content on the interest in buying fashion for village youth by Makmur, 2) there was a positive and significant effect of OOTD Style creator content on the interest in buying fashion for village youth by Makmur, 3) there is a positive and significant effect of video visualization of TikTok content and OOTD Style of creator content on the interest in buying fashion for village youth by Makmur.